Optimization of Operational Parameters in Nickel–Cobalt Electrowinning from Mixed Sulfate Electrolytes - Subandrio, Subandrio; Widodo, Nur Lestari; Kirana, Andi Mutia Putri; Rozafia, Ade Irma; Karimah, Nur; Farida, Nor; Dahani, Wiwik; Rosyidah, Afifah; Utomo, Wahyu Prasetyo; Hartanto, Djoko (Trends in Sciences, 2026)
Nickel and cobalt are strategic metals that play an important role in the development of electric vehicle batteries and high-performance metal alloys. Indonesia, as one of the countries with the largest laterite nickel reserves in the world, faces challenges in the efficient, selective, and environmentally friendly extraction process. Conventional separation methods such as solvent extraction have drawbacks, including high cost and the chemical waste generated. Therefore, the electrowinning method becomes a promising alternative because it can produce high-purity metals with lower energy consumption. This research aims to optimize the process of electrowinning mixed nickel and cobalt from sulfate solution by varying electrode distance, applied potential, and metal ion concentration ratio to improve deposition efficiency and selectivity of the resulting metals. The process was conducted using a batch electrolysis cell with nickel-cobalt sulfate electrolyte and boric acid buffer. The research results indicate that increasing the potential and decreasing the electrode distance significantly increase the mass of the metal deposit, whereas the Ni-Co concentration ratio affects reduction selectivity due to differences in ion mobility and overpotential for each metal. XRD analysis shows that the crystal phase formed is dominated by nickel with a face-centered cubic (FCC) structure and cobalt with a hexagonal close-packed (HCP) structure. Increasing the potential leads to a decrease in crystallinity due to the high nucleation rate. FESEM observation results show that the particle morphology is non-uniform with a flower-like aggregate shape, while EDX analysis indicates that the deposit composition is dominated by nickel at 86.9% and cobalt at 13.1% with uniform element distribution. These results indicate that optimal electrowinning conditions are capable of producing homogeneous nickel and cobalt metal deposits with high efficiency. HIGHLIGHTS Electrowinning optimized for Ni-Co sulfate system with varied potential, electrode distance, and concentration ratio of Ni:Co in the electrolyte. Higher potential and nickel concentrations with shorter electrode distance increased metal deposition efficiency. The longer electrode distance enhances the separation of nickel and cobalt in the deposit, increasing the selectivity for nickel. XRD patterns confirmed FCC nickel phase and HCP cobalt phase FESEM and EDX analysis revealed flower-like aggregates dominated by nickel element. GRAPHICAL ABSTRACT